Використання iot пристроїв для покращення медичних послуг - Калякіна, Є. О. (ХНУРЕ, 2020)
Medical IoT refers to a growing number of IoT uses in the medical industry. Today, a wide range of IoT applications and devices specifically designed for the needs and settings of healthcare, such as sensors and applications for remote monitoring, consultation and delivery in the field of healthcare, are being developed. Broader IoT use cases can also apply to healthcare, such as leveraging IoT connectivity to monitor critical medical devices and equipment, and to receive alerts when they require maintenance or replacement.
Keywords: IoT датчики; RTM; медичні діагностичні системи